Phosphogypsum-based geopolymer grouting material and preparation method thereof

CN118459157BActive Publication Date: 2026-10-27CHANGAN UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410582474.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-11
Publication Date
2026-10-27
Estimated Expiration
2044-05-11

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种磷石膏基地聚合物道路灌浆胶结料及制备方法,解决了现有灌浆胶结料成本高的问题

Benefits of technology

[0032]本发明公开了一种磷石膏基地聚合物灌浆材料,以磷石膏、陶瓷废料、偏高岭土和铁尾矿砂为原材料,通过碱激发作用制成灌浆材料代替传统水泥基灌浆材料,碱激发作用生成三维网状硅铝盐酸凝胶立体结构,将重金属离子固化在三维网状硅铝盐酸凝胶立体结构中。不仅减少水泥和天然砂用量,降低道路灌浆施工成本,缓解建筑材料需求紧张问题;本发明通过磷石膏、陶瓷废料和铁尾矿砂多种固体废料间的协同作用,将其转化为建筑材料,避免了磷石膏、陶瓷废料和铁尾矿砂堆放带来的环境污染等问题,同时减轻了道路工程对水泥的需求量,达到了固体废料消耗、节约资源和减少施工成本的目的,具有显著的经济与社会效益。工作性能、力学性能和耐久性满足规范要求,最重要的是减少了水泥用量,大宗消耗磷石膏、陶瓷废料和铁尾矿等固废,对于环境保护、节能减排具有重要意义。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118459157B_ABST
    Figure CN118459157B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of highway engineering, and particularly relates to a phosphogypsum-based geopolymer grouting material, which is a three-dimensional network silicon-aluminum salt hydrochloric gel three-dimensional structure, and raw materials of the phosphogypsum-based geopolymer grouting material include the following components in percentage by mass: phosphogypsum 16.86-19.11%, ceramic waste 7.81-8.60%, metakaolin 9.28-10.51%, alkali activator 4.38-5.22%, distilled water 8.41-9.44%, waterproof additive 0.34-0.37%, and iron tailings 47.78-51.89%. A preparation method of the phosphogypsum-based geopolymer grouting material is also disclosed, which not only reduces the cement and natural sand consumption and the road grouting construction cost, and relieves the problem of tight demand for building materials, but also converts the solid waste such as phosphogypsum, ceramic waste and iron tailings into building materials through the synergistic effect among the solid waste, and avoids the environmental pollution caused by the storage of the phosphogypsum, ceramic waste and iron tailings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of highway engineering technology, specifically relating to a phosphogypsum-based polymer grouting material and its preparation method. Background Technology

[0002] Road grouting materials are engineering materials used to fill internal spaces such as cracks and pores, and possess a certain degree of bonding ability. Currently, the most common grouting materials include cementitious adhesives, fly ash cement adhesives, and cement-water glass adhesives. However, cement-based grouting materials have disadvantages such as high bleeding rate, long setting time, poor stability, and high price. Furthermore, cement production generates a large amount of CO2 gas, which is inconsistent with the current green and environmentally friendly development concept of low-carbon development. In addition, road construction requires a large amount of cement, leading to an increasing supply-demand imbalance and frequent shortages, severely impacting construction progress. A new type of green cementitious material, using aluminosilicates such as natural minerals and industrial solid waste as raw materials, undergoes a polymerization reaction under the action of an alkali activator to form an amorphous three-dimensional spatial network structure similar to zeolite. Due to its excellent mechanical properties, acid and alkali resistance, fire resistance, high temperature resistance, and low cost, it has the characteristics of replacing traditional cement and making full use of mineral waste and construction waste as raw materials.

[0003] Phosphogypsum is an industrial solid waste generated during the production of phosphoric acid when sulfuric acid acts on powdered phosphate rock. Its main component is sulfuric acid dihydrate (CaSO4·2H2O). In recent years, with the advancement of sustainable development concepts and environmental protection themes, scholars at home and abroad have begun to study geopolymers to treat phosphogypsum. However, most of these studies still require the addition of traditional cement during preparation, resulting in high costs for existing grouting binders, and there is a lack of research on the large-scale application of phosphogypsum in road engineering construction. Summary of the Invention

[0004] The purpose of this invention is to provide a phosphogypsum-based polymer road grout binder and its preparation method, which solves the problem of high cost of existing grout binders.

[0005] This invention is achieved through the following technical solution:

[0006] A phosphogypsum-based polymer road grouting material, by mass percentage, comprises the following components:

[0007] Phosphogypsum 16.86%-19.11%, ceramic waste 7.81%-8.60%, metakaolin 9.28%-10.51%, alkali activator 4.38%-5.22%, distilled water 8.41%-9.44%, waterproofing additive 0.34%-0.37%, iron tailings sand 47.78%-51.89%;

[0008] The phosphogypsum-based polymer road grouting material has a three-dimensional network structure of silica-alumina hydrochloric acid gel.

[0009] Furthermore, the unconfined compressive strength, flexural strength, and splitting tensile strength of the phosphogypsum-based polymer road grouting material after 28 days of curing reach 5.84-11.56 MPa, 0.61-2.41 MPa, and 0.32-0.67 MPa, respectively.

[0010] Furthermore, the fluidity of the phosphogypsum-based polymer road grouting material reaches 199-235 mm, the setting time reaches 214-387 min, and the water bleeding rate reaches 0.2%-0.9%.

[0011] Furthermore, the impermeability pressure of the phosphogypsum-based polymer road grouting material reached a maximum of 1.1 MPa after 28 days of curing.

[0012] Furthermore, the alkali activator is a compound of sodium hydroxide and sodium silicate.

[0013] Furthermore, the waterproofing additive is a sodium methylsilicate solution.

[0014] Furthermore, ceramic waste, metakaolin, and phosphogypsum constitute the adhesive material system, and the mass ratio of water to the weight of the adhesive material system is 0.22-0.28.

[0015] The weight ratio of the adhesive material system to the iron tailings sand is 0.65-0.80;

[0016] The weight ratio of the phosphogypsum, ceramic waste, and metakaolin is 1:0.45:0.55.

[0017] Furthermore, the particle size of the phosphogypsum is between 0.1 and 600 μm, and the content of phosphogypsum particles with a particle size of less than 200 μm is ≥84%.

[0018] The ceramic waste mainly consists of SiO2 and Al2O3, with a combined content of ≥88%.

[0019] The particle size of the ceramic waste is 15-45 μm;

[0020] The metakaolin mainly consists of SiO2 and Al2O3, with a combined content of ≥97.39%.

[0021] The iron tailings sand is a solid waste discharged after iron ore is refined. It is obtained through processes such as crushing, grinding, washing and refining. The particle size of the iron tailings sand is concentrated in the range of 0.36-0.85mm.

[0022] This invention also discloses a method for preparing a phosphogypsum-based polymer grouting material, comprising the following steps:

[0023] (1) Preparation:

[0024] Prepare the alkali activator in advance and age it for later use. Weigh out the required mass of phosphogypsum, ceramic waste, metakaolin, alkali activator, distilled water, waterproofing additive and iron tailings sand.

[0025] (2) Preparation of geopolymer grouting materials:

[0026] The weighed phosphogypsum, ceramic waste, metakaolin and iron tailings sand are mixed and stirred. Then, an alkali activator and a waterproofing additive are added and stirred evenly to obtain a phosphogypsum-based polymer grouting material.

[0027] Furthermore, the preparation process of the alkali activator is as follows:

[0028] Weigh out the required mass of flake NaOH and instant sodium silicate granules;

[0029] Add the instant sodium silicate granules to distilled water in several batches, stirring after each addition until the solution becomes cloudy, uniform, and free of precipitate, then continue adding.

[0030] Pour flake NaOH into a sodium silicate solution and stir magnetically until the liquid is uniform in color and free of flocculent precipitate to obtain an alkaline activator.

[0031] Compared with the prior art, the present invention has the following beneficial technical effects:

[0032] This invention discloses a phosphogypsum-based polymer grouting material. Using phosphogypsum, ceramic waste, metakaolin, and iron tailings as raw materials, it is produced through alkali activation to replace traditional cement-based grouting materials. The alkali activation process generates a three-dimensional network of silica-alumina hydrochloric acid gel, solidifying heavy metal ions within this structure. This not only reduces the amount of cement and natural sand used, lowering road grouting construction costs and alleviating the shortage of building materials, but also utilizes the synergistic effect of various solid wastes—phosphogypsum, ceramic waste, and iron tailings—to transform them into building materials. This avoids the environmental pollution problems caused by the stockpiling of phosphogypsum, ceramic waste, and iron tailings, while simultaneously reducing the demand for cement in road construction. It achieves the goals of solid waste consumption, resource conservation, and reduced construction costs, demonstrating significant economic and social benefits. The workability, mechanical properties, and durability meet the required specifications. Most importantly, it reduces cement usage and consumes large quantities of solid waste such as phosphogypsum, ceramic waste, and iron tailings, which is of great significance for environmental protection, energy conservation, and emission reduction.

[0033] Hydration mechanism and strength source: Under alkaline activator solution, OH - The ions break the covalent bonds such as Si-O-Si, Al-O-Al, and Ca-O in ceramic waste and metakaolin, dissolving a large amount of Si and Al monomers, which then combine with oxygen to form [SiO4].4- and [AlO4] 5- Ionic clusters. Next, the dissolved [SiO4]... 4- and [AlO4] 5- Anionic groups and Ca in solution 2+ First, transitional oligomers are formed. Finally, with increasing curing time, the generated silicate oligomers continue to polymerize, further forming a three-dimensional network of hydrated calcium aluminosilicate gel (CASH) composed of silicon (aluminum) oxygen tetrahedra. Furthermore, as the polymerization reaction progresses, the phosphogypsum and slag present in the reaction system dissolve a large amount of Ca. 2+ and SO4 2- Ions, Ca 2+ It will react with [SiO4] 4- A hydration reaction will directly occur to form amorphous hydrated calcium silicate gel (CSH). Simultaneously, under alkaline conditions, a large amount of CaSO4·2H2O will act as a sulfate activator on the slag material, combining with the Ca in the reaction system. 2+ And the dissolved Al 3+ The monomeric ions further generate crystalline hydrated product ettringite (AFt). These calcium aluminosilicate gels (CASH), calcium silicate gels (CSH), and ettringite (AFt) coexist and combine to form a denser three-dimensional network structure, increasing the contact area and adhesion between the gel product and the aggregate. At the same time, the gel particles fill the particle pores, greatly reducing porosity. The overall internal structure becomes more compact and the porous structure disappears, resulting in increased mechanical strength on a macroscopic level.

[0034] The solidification mechanism of phosphogypsum grouting materials for toxic ions mainly involves physical adsorption and encapsulation, chemical displacement, and precipitation: First, the three-dimensional network structure of the gel solidifies and stabilizes toxic ions through physical adsorption and encapsulation; second, the heavy metal cations As... 5+ Pb 2+ and Cr 3+ Will participate in balancing AI 3+ The excess negative charge generated in the four-coordinate state is thus fixed in the skeletal structure of the gel; thirdly, water-soluble F - and PO4 3- It will react with Ca in the reaction system 2+ Under alkaline conditions, insoluble precipitates such as CaF2 and Ca2(PO4)3 are generated, thereby achieving solidification and stability.

[0035] The phosphogypsum-based polymer road grout binder has high compressive and flexural strength, good fluidity and impermeability, low heavy metal leaching concentration, and minimal environmental impact. The mechanical strength, workability, and durability of the phosphogypsum-based polymer road grout binder meet the requirements for roadbed reinforcement.

[0036] Furthermore, after 28 days of curing, the unconfined compressive strength, flexural strength, and splitting tensile strength of the phosphogypsum-based polymer grouting material described in this invention can reach 11.56 MPa, 2.41 MPa, and 0.67 MPa, respectively. The mechanical properties are excellent and fully meet the strength requirements for the grouting material when used for roadbed reinforcement and treatment of defects such as voids. It can resist groundwater erosion and surrounding pressure after early grouting, thereby achieving the expected reinforcement effect.

[0037] The phosphogypsum-based polymer grouting material prepared by this invention exhibits excellent performance: the fluidity, initial and final setting times, and bleeding rate of the grouting material meet the requirements of specification DG / TG 08-2240-2017. Compared with existing grouting materials, it has better durability, with a 28-day impermeability pressure of 1.1 MPa, and the leaching amount of harmful substances meets environmental protection requirements.

[0038] Furthermore, ceramic waste, metakaolin, and phosphogypsum constitute the adhesive material system. A small amount of water affects the formation of hydration products, but excessive water usage reduces the alkalinity of the geopolymer reaction system, affecting the hydration reaction rate and setting time. To ensure the mechanical properties of the geopolymer binder, the water-to-binder ratio is set within the range of 0.22-0.28.

[0039] The added iron tailings particles, due to their continuous gradation, act as a skeletal support in the grouting material. Furthermore, the cementitious materials in the grout not only adhere to the surface of the sand particles but also fill the voids in the skeletal structure, increasing the particle bonding force and significantly improving the overall density of the grout's internal structure. However, excessive sand particle content leads to lower fluidity, lower strength, and increased water permeability in the grouting material. Therefore, the specified range for the weight ratio of the cementitious material system to the iron tailings sand is 0.65-0.80.

[0040] Excessive use of phosphogypsum, coupled with the lack of reactive components SiO2 and Al2O3 in the geopolymer reaction, hinders the formation of a stable internal structure and results in lower strength. Excessive use of ceramic waste and metakaolin dissolves large amounts of Si and Al monomers, accelerating the geopolymer hydration reaction, promoting the formation of hydration gel products, and increasing the density of the internal structure of the solidified geopolymer, thus improving strength. However, an excessively high mass ratio of ceramic waste and metakaolin severely shortens the geopolymer's setting time, making it difficult to apply in engineering projects. To avoid these issues, the weight ratio of phosphogypsum, ceramic waste, and metakaolin is set at 1:0.45:0.55.

[0041] Furthermore, iron tailings are solid waste discharged after iron ore refining, produced through further crushing, grinding, and washing processes. The annual discharge of iron tailings reaches as high as 150 million tons, with a utilization rate of only 7%. The large accumulation of iron tailings not only pollutes the air and water but also poses safety problems. Since the chemical composition and mineral composition of iron tailings are basically similar to those of natural sand, using iron tailings as a substitute for natural sand in grouting materials can not only solve the environmental and safety problems caused by iron tailings but also alleviate the shortage of natural sand resources. Currently, it has not been applied in road engineering.

[0042] The present invention also discloses a method for preparing the phosphogypsum-based polymer grouting material, which involves mixing various materials, has a simple preparation process, does not require high-end equipment, and has low production costs. Attached Figure Description

[0043] Figure 1 Flowchart for the preparation of polymer grouting materials for phosphogypsum base;

[0044] Figure 2 The image shows a SEM image of the phosphogypsum-based polymer grouting material in Example 1. Detailed Implementation

[0045] To make the objectives, technical solutions, and advantages of the present invention clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention; that is, the described embodiments are only a part of the embodiments of the present invention, and not all of them.

[0046] The components described and illustrated in the accompanying drawings and embodiments of this invention can be arranged and designed in various different configurations. Therefore, the detailed description of the embodiments of the invention provided in the following drawings is not intended to limit the scope of the claimed invention, but merely to illustrate one selected embodiment of the invention. All other embodiments obtained by those skilled in the art based on the accompanying drawings and embodiments of this invention without inventive effort are within the scope of protection of this invention.

[0047] It should be noted that the terms “comprising,” “including,” or any other variations are intended to cover non-exclusive inclusion, such that a process, element, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to the process, element, method, article, or apparatus.

[0048] Unless otherwise specified, the test methods described in the following examples are generally performed under standard conditions or as recommended by the respective manufacturers.

[0049] The present invention provides a phosphogypsum-based polymer road grouting material, which comprises the following raw materials by mass percentage:

[0050] Phosphogypsum 16.86%-19.11%, ceramic waste 7.81%-8.60%, metakaolin 9.28%-10.51%, alkali activator 4.38%-5.22%, distilled water 8.41%-9.44%, waterproofing additive 0.34%-0.37%, iron tailings sand 47.78%-51.89%.

[0051] In this invention, the alkali activator of the phosphogypsum-based polymer grouting material is a compound of sodium hydroxide and sodium silicate.

[0052] The waterproofing additive is a sodium methylsilicate solution.

[0053] The weight ratio of water to ceramic waste, metakaolin, and phosphogypsum, i.e., the water-binder ratio, is 0.22-0.28.

[0054] The total weight ratio of the phosphogypsum, ceramic waste, and metakaolin to the iron tailings sand, i.e., the mortar-sand ratio, is 0.65-0.80.

[0055] The weight ratio of the phosphogypsum, ceramic waste, and metakaolin is 1:0.45:0.55.

[0056] In this invention, the particle size of the phosphogypsum is between 0.1 and 600 μm, and the content of phosphogypsum particles with a particle size of less than 200 μm is ≥84%.

[0057] In this invention, the main components of the ceramic waste, SiO2 and Al2O3, contain ≥88% content; the particle size of the ceramic waste is between 15-45μm.

[0058] In this invention, the content of the main components of metakaolin, SiO2 and Al2O3, is ≥97.39%.

[0059] In this invention, the sodium methylsilicate has a purity of ≥99%.

[0060] In this invention, the iron tailings sand is the solid waste discharged after the iron ore is refined. It is obtained through processes such as crushing, grinding, washing and refining. The particle size of the iron tailings sand is concentrated in the range of 0.36-0.85mm.

[0061] In this invention, the sodium hydroxide has a purity of ≥90%.

[0062] In this invention, the sodium silicate is a fast-dissolving powdered sodium silicate; the dissolution rate of the sodium silicate is ≤240s at 30℃; the sieve pass rate of the sodium silicate at 120 mesh is ≥95%; and the modulus of the sodium silicate is ≥3.0.

[0063] Ceramic waste is powder produced from waste daily-use ceramics, waste floor tiles, etc. through crushing, washing and refining, and grinding in a ball mill. Its main components are SiO2, Al2O3, CaO, etc. It contains high content of active silicon and aluminum components and has good high temperature resistance and corrosion resistance. Therefore, it can be used to prepare geopolymers.

[0064] Iron tailings are solid waste discharged after iron ore refining, produced through further crushing, grinding, and washing processes. Annual iron tailings discharge reaches 150 million tons, with a utilization rate of only 7%. The large accumulation of iron tailings not only pollutes the air and water but also poses safety problems. On the other hand, with the development of infrastructure in China, natural sand resources are becoming increasingly scarce. Various regions have begun to issue bans on the mining of natural sand to protect the environment, making natural sand increasingly expensive, and its supply cannot meet the requirements of engineering construction. Iron tailings have a chemical composition and mineral composition that are basically similar to natural sand. Therefore, using iron tailings as a substitute for natural sand in grouting materials can not only solve the environmental and safety problems caused by iron tailings but also alleviate the shortage of natural sand resources. Currently, its application in road engineering is extremely rare.

[0065] This invention improves the water stability and durability of phosphogypsum-based polymers and applies them to road engineering, providing a basis for the large-scale and high-value utilization of various solid wastes; it reduces the cost of existing grouting materials; and the cured phosphogypsum-based polymer road grout binder can effectively solidify and stabilize the toxic substances precipitated from phosphogypsum, reducing the risk of groundwater pollution.

[0066] like Figure 1 As shown, the present invention also provides a method for preparing the phosphogypsum-based polymer grouting material for roadbed reinforcement and maintenance, comprising the following steps:

[0067] (1) Preparation:

[0068] Preparation of alkali activator: Take a beaker of appropriate size and weigh out the required mass of distilled water; take two small beakers and weigh out the corresponding masses of flake NaOH and instant sodium silicate granules; add the instant sodium silicate granules to the distilled water in 2-3 portions, stirring with a glass rod each time until the solution becomes cloudy, uniform, and free of precipitate before continuing to add; pour the flake NaOH from the small beakers into the above liquid (releasing a large amount of heat, so be careful), and then use a magnetic stirrer to stir thoroughly at low speed for 10 minutes until the liquid is uniform in color and free of flocculent precipitate, thus obtaining the alkali activator.

[0069] Prepare the alkali activator in advance and age it for later use. Weigh the required mass of phosphogypsum, ceramic waste, metakaolin, alkali activator, distilled water, waterproofing additive and iron tailings sand according to the test requirements. Check and verify the instruments used, clean and dry the cement mortar mixing pot, and set it aside for use.

[0070] (2) Preparation of geopolymer grouting material: Weighed phosphogypsum, ceramic waste, metakaolin and iron tailings sand are poured into a dry cement paste mixing pot and stirred for 1 minute. Then, the pre-prepared alkali activator and waterproofing admixture are added and stirred evenly to obtain phosphogypsum-based polymer grouting material. In this invention, the proportions of each component in the geopolymer grouting material are as follows: phosphogypsum 16.86%-19.11%, ceramic waste 7.81%-8.60%, metakaolin 9.28%-10.51%, alkali activator 4.38%-5.22%, distilled water 8.41%-9.44%, waterproofing admixture 0.34%-0.37%, and iron tailings sand 47.78%-51.89%.

[0071] The weight ratio of water to the total weight of ceramic waste, metakaolin, and phosphogypsum, i.e., the water-cement ratio, is 0.22-0.28; the weight ratio of the total weight of phosphogypsum, ceramic waste, and metakaolin to the weight of iron tailings sand, i.e., the cement-sand ratio, is 0.67-0.80; the weight ratio of phosphogypsum, ceramic waste, and metakaolin is 1:0.45:0.55; and the grouting material has good fluidity.

[0072] (3) Molding and curing: Before the experiment, clean the inside and surface of the mold, then apply machine oil evenly to its inner wall. After the geopolymer grouting material is mixed, pour it into the mold to 1 / 2 height, place it on the vibration table and vibrate for 1 minute, then fill the mold and vibrate for another 1 minute. Then use a scraper to smooth the surface to ensure that no air bubbles are generated. After the specimen is molded, let it stand at room temperature for 24 hours before demolding to obtain the molded specimen.

[0073] The molded specimens are placed in a standard curing chamber and cured at standard curing temperature and humidity until the specified age. In this invention, the preferred temperature is 20±5℃ and the relative humidity is above 95%; the specified curing age is 3 days, 7 days, 14 days, and 28 days, respectively.

[0074] In this invention, the performance of the phosphogypsum-based grouting material meets the technical requirements for grouting in road construction; its strength characteristics meet the strength required for roadbed reinforcement and treatment of defects such as voids; it resists groundwater erosion and surrounding pressure after early grouting; its durability, such as impermeability and freeze-thaw resistance, is higher than some existing cement-based grouting materials; its heavy metal curing characteristics meet the environmental protection requirements of different grades of highways, and its construction cost is lower than that of cement-based grouting materials.

[0075] To better understand the present invention, the following embodiments further illustrate the content of the present invention, but the present invention is not limited to the following embodiments.

[0076] Example 1

[0077] (1) Preparation:

[0078] Prepare the alkali activator in advance:

[0079] Take a beaker of suitable size and weigh out the required mass of distilled water. Add the weighed, readily soluble sodium silicate granules to the distilled water in 2-3 portions, stirring with a glass rod after each addition until the solution becomes uniform in color and free of precipitate before continuing. Pour the flake-shaped NaOH from the small beaker into the above liquid (this releases significant heat; caution is advised). Then, use a magnetic stirrer to stir thoroughly at low speed for 10 minutes until the liquid is uniform in color and free of flocculent precipitate. Finally, remove the well-stirred mixture, seal the mouth of the beaker with polyethylene film, and age for 3 hours to obtain the alkali activator. The mass ratio of sodium hydroxide to readily soluble sodium silicate is 0.4.

[0080] According to mass percentages, 19.11% phosphogypsum, 8.60% ceramic waste, 10.51% metakaolin, 5.22% alkali activator, 8.41% water, 0.37% sodium methylsilicate, and 47.78% iron tailings were weighed out, i.e., the weight ratio of water to ceramic waste, metakaolin, and phosphogypsum was 0.22; the total weight ratio of phosphogypsum, ceramic waste, and metakaolin to iron tailings was 0.8; and the weight ratio of phosphogypsum, ceramic waste, and metakaolin was 1:0.45:0.55.

[0081] Check and verify the instruments used, clean and dry the cement mortar mixing pot, and set it aside for use.

[0082] (2) Preparation of geopolymer grouting materials:

[0083] The weighed phosphogypsum, metakaolin, ceramic waste and iron tailings sand are poured into a dry cement paste mixing pot and stirred for 1 minute. Then, the pre-prepared alkali activator and waterproofing additive are added and stirred evenly to obtain the phosphogypsum-based polymer grouting material.

[0084] (3) Molding and Curing:

[0085] Before the experiment, clean the inside and surface of the mold, then apply machine oil evenly to its inner wall. After the geopolymer grouting material is mixed, pour it into the mold to half its height, place it on the vibration table and vibrate for 1 minute. Then fill the mold and vibrate for another minute. After that, use a scraper to smooth the surface to ensure that no air bubbles are generated. After the specimen is molded, let it stand at room temperature for 24 hours before demolding to obtain the molded specimen.

[0086] The molded specimens were placed in a standard curing chamber and cured for 3 days, 7 days, 14 days, and 28 days at a temperature of 20±5℃ and a relative humidity of ≥95%. Their working properties, such as fluidity, setting time, and water seepage, as well as their strengths at 3 days, 7 days, 14 days, and 28 days, including unconfined compressive strength, flexural strength, and splitting tensile strength, and their durability properties, such as impermeability, freeze-thaw resistance, and heavy metal leaching characteristics, were tested. The test results are shown in Table 1.

[0087] As shown in Table 1, the fluidity, setting time, and bleeding properties of the phosphogypsum-based polymer grouting material prepared in this embodiment all meet the technical requirements of DG / TJ 08-2240-2017. The 28-day unconfined compressive strength of the specimen is 11.56 MPa, which meets the technical requirement of DG / TJ 08-2240-2017 that the 28-day compressive strength of the grouting material should not be less than 4.2 MPa. The leachate from the specimen contains As, Pb, Cr, and F... - and PO4 3- The concentrations of the ions were 0 μg / L, 2.36 μg / L, 13.13 μg / L, 0.3 mg / L, and 0.14 mg / L, respectively. The concentrations of As, Pb, Cr, and F in the specimen were... - and PO4 3- The ion concentrations of [specific compounds] are significantly lower than those of phosphogypsum. Specifically, the Pb ion concentration is lower than the concentration limit of GB / T14848-2017(II) (5 μg / L), the Cr ion concentration is lower than the concentration limit of GB / T14848-2017(III) (50 μg / L), and the F [specific ion concentration] is lower. - The ion concentration is less than the concentration limit (1 μg / L) of GB / T14848-2017(Ⅱ). The phosphogypsum-based polymer grouting material exhibits good working performance (flowability, setting time, and bleeding rate), mechanical properties (compressive strength, flexural strength, and splitting tensile strength), and durability (resistance to seepage pressure), meeting the requirements for road grouting materials.

[0088] Depend on Figure 2 (a) It can be seen that the microstructure of the phosphogypsum grouting material with a mortar-to-gel ratio of 0.60 contains a small number of sand particles that are not encapsulated by the flocculent gel products. The pores between the particles are relatively large, resulting in a small number of amorphous flocculent gel products and a relatively loose overall internal structure. Figure 2 (b) It can be seen that when the mortar-to-gel ratio is 0.65, all sand particles are covered by gel products, the amount of amorphous flocculent gel products CASH and CSH increases, some small gel particles connect and aggregate into large gel particles, and columnar hydration products AFt fill the pores between particles, resulting in a denser overall internal structure. Figure 2In (c) and (d), when the mortar-to-gel ratio increases to 0.70 and 0.75, the surface of the phosphogypsum grouting material is filled with hydration gel products CASH, CSH, and AFt. These gel products coexist and combine to form a denser three-dimensional network structure, increasing the contact area and adhesion between the gel products and the aggregate. Simultaneously, the gel particles fill the particle pores, significantly reducing porosity. The overall internal structure becomes more compact and porous, resulting in increased macroscopic mechanical strength. The solidification mechanism of phosphogypsum grouting material for toxic ions mainly involves physical adsorption and encapsulation, chemical displacement, and precipitation: First, the three-dimensional network structure of the gel solidifies and stabilizes toxic ions through physical adsorption and encapsulation; second, the heavy metal cation As... 5+ Pb 2+ and Cr 3+ Will participate in balancing AI 3+ The excess negative charge generated in the four-coordinate state is thus fixed in the skeletal structure of the gel; thirdly, water-soluble F - and PO4 3- It will react with Ca in the reaction system 2+ Under alkaline conditions, insoluble precipitates such as CaF2 and Ca2(PO4)3 are generated, thereby achieving solidification and stability.

[0089] Example 2

[0090] (1) Preparation:

[0091] Preparation of alkali activator: Take a beaker of appropriate size and weigh out the required mass of distilled water. Add the weighed instant sodium silicate granules to the distilled water in 2-3 portions, stirring with a glass rod each time until the solution becomes uniform in color and free of precipitate before adding more. Pour the flake NaOH from the small beaker into the above liquid (this releases a large amount of heat, so be careful). Then, use a magnetic stirrer to stir thoroughly at low speed for 10 minutes until the liquid is uniform in color and free of flocculent precipitate. Finally, remove the well-stirred mixture, seal the mouth of the beaker with polyethylene film, and age for 3 hours to obtain the alkali activator.

[0092] Weigh out the following components according to their mass fractions: 18.43% phosphogypsum, 8.29% ceramic waste, 10.13% metakaolin, 4.79% alkali activator, 8.84% water, 0.37% waterproofing additive, and 49.15% iron tailings sand. The weight ratio of water to ceramic waste, metakaolin, and phosphogypsum is 0.24; the total weight ratio of phosphogypsum, ceramic waste, and metakaolin to iron tailings sand is 0.75; and the weight ratio of phosphogypsum, ceramic waste, and metakaolin is 1:0.45:0.55. Check and verify the instruments used, clean and dry the cement mortar mixing pot, and set aside for use.

[0093] (2) Preparation of geopolymer grouting material: Pour the weighed phosphogypsum, metakaolin, ceramic waste and iron tailings into a dry cement paste mixing pot and stir for 1 minute. Then pour in the pre-prepared alkali activator and waterproofing additive and stir evenly to obtain phosphogypsum-based polymer grouting material.

[0094] (3) Molding and curing: Before the experiment, clean the inside and surface of the mold, then apply machine oil evenly to its inner wall. After the geopolymer grouting material is mixed, pour it into the mold to 1 / 2 height, place it on the vibration table and vibrate for 1 minute, then fill the mold and vibrate for another 1 minute. Then use a scraper to smooth the surface to ensure that no air bubbles are generated. After the specimen is molded, let it stand at room temperature for 24 hours before demolding to obtain the molded specimen.

[0095] The molded specimens were placed in a standard curing chamber and cured for 3 days, 7 days, 14 days, and 28 days at a temperature of 20±5℃ and a relative humidity of ≥95%. Their working properties, such as fluidity, setting time, and water seepage, as well as their strengths at 3 days, 7 days, 14 days, and 28 days, including unconfined compressive strength, flexural strength, and splitting tensile strength, and their durability properties, such as impermeability, freeze-thaw resistance, and heavy metal leaching characteristics, were tested. The test results are shown in Table 1.

[0096] As shown in Table 1, the fluidity, setting time, and bleeding properties of the phosphogypsum-based polymer grouting material prepared in this embodiment all meet the technical requirements of DG / TJ 08-2240-2017. The 28-day unconfined compressive strength of the specimen is 9.55 MPa, which meets the technical requirement of DG / TJ 08-2240-2017 that the 28-day compressive strength of the grouting material should not be less than 4.2 MPa. The leachate from the specimen contains As, Pb, Cr, and F... - and PO4 3- The concentrations of the ions were 0.40 μg / L, 3.91 μg / L, 16.74 μg / L, 0.58 mg / L, and 0.26 mg / L, respectively. The concentrations of As, Pb, Cr, and F in the specimen were... - and PO4 3- The ion concentrations of [specific ions] are significantly lower than those of phosphogypsum. Specifically, the As ion concentration is lower than the concentration limit of GB / T14848-2017(II) (1 μg / L), the Pb ion concentration is lower than the concentration limit of GB / T14848-2017(II) (5 μg / L), the Cr ion concentration is lower than the concentration limit of GB / T14848-2017(III) (50 μg / L), and the F [ion concentration] is lower than the concentration limit of [specific ions]. -The ion concentration is less than the concentration limit (1 μg / L) of GB / T14848-2017(Ⅱ). The phosphogypsum-based polymer grouting material exhibits good working performance (flowability, setting time, and bleeding rate), mechanical properties (compressive strength, flexural strength, and splitting tensile strength), and durability (resistance to seepage pressure), meeting the requirements for road grouting materials.

[0097] Example 3

[0098] (1) Preparation:

[0099] Preparation of alkali activator: Take a beaker of appropriate size and weigh out the required mass of distilled water. Add the weighed instant sodium silicate granules to the distilled water in 2-3 portions, stirring with a glass rod each time until the solution becomes uniform in color and free of precipitate before adding more. Pour the flake NaOH from the small beaker into the above liquid (this releases a large amount of heat, so be careful). Then, use a magnetic stirrer to stir thoroughly at low speed for 10 minutes until the liquid is uniform in color and free of flocculent precipitate. Finally, remove the well-stirred mixture, seal the mouth of the beaker with polyethylene film, and age for 3 hours to obtain the alkali activator.

[0100] Weigh out 17.68% phosphogypsum, 7.95% ceramic waste, 9.73% metakaolin, 4.39% alkali activator, 9.19% water, 0.35% waterproofing additive, and 50.71% iron tailings sand according to their respective mass fractions. That is, the weight ratio of water to ceramic waste, metakaolin, and phosphogypsum is 0.26; the weight ratio of the total weight of phosphogypsum, ceramic waste, and metakaolin to iron tailings sand is 0.70; and the weight ratio of phosphogypsum, ceramic waste, and metakaolin is 1:0.45:0.55. Check and verify the instruments used, clean and dry the cement mortar mixing pot, and set it aside for use.

[0101] (2) Preparation of geopolymer grouting material: Pour the weighed phosphogypsum, metakaolin, ceramic waste and iron tailings into a dry cement paste mixing pot and stir for 1 minute. Then pour in the pre-prepared alkali activator and waterproofing additive and stir evenly to obtain phosphogypsum-based polymer grouting material.

[0102] (3) Molding and curing: Before the experiment, clean the inside and surface of the mold, then apply machine oil evenly to its inner wall. After the geopolymer grouting material is mixed, pour it into the mold to 1 / 2 height, place it on the vibration table and vibrate for 1 minute, then fill the mold and vibrate for another 1 minute. Then use a scraper to smooth the surface to ensure that no air bubbles are generated. After the specimen is molded, let it stand at room temperature for 24 hours before demolding to obtain the molded specimen.

[0103] The molded specimens were placed in a standard curing chamber and cured for 3 days, 7 days, 14 days, and 28 days at a temperature of 20±5℃ and a relative humidity of over 95%. Their workability, such as fluidity, setting time, and water leakage, as well as their strength at 3 days, 7 days, 14 days, and 28 days (unconfined compressive strength, flexural strength, and splitting tensile strength), and durability properties (impermeability, freeze-thaw resistance, and heavy metal leaching characteristics) were tested. The test results are shown in Table 1.

[0104] As shown in Table 1, the fluidity, setting time, and bleeding properties of the phosphogypsum-based polymer grouting material prepared in this embodiment all meet the technical requirements of DG / TJ 08-2240-2017. The 28-day unconfined compressive strength of the specimen is 7.86 MPa, which meets the technical requirement of DG / TJ 08-2240-2017 that the 28-day compressive strength of the grouting material should not be less than 4.2 MPa. The leachate from the specimen contains As, Pb, Cr, and F... - and PO4 3- The concentrations of the ions were 1.59 μg / L, 4.62 μg / L, 19.2 μg / L, 0.64 mg / L, and 0.49 mg / L, respectively. The concentrations of As, Pb, Cr, and F in the specimen were... - and PO4 3- The ion concentrations of [specific ions] are significantly lower than those of phosphogypsum. Specifically, the As ion concentration is lower than the concentration limit of GB / T14848-2017(III) (10 μg / L), the Pb ion concentration is lower than the concentration limit of GB / T14848-2017(II) (5 μg / L), the Cr ion concentration is lower than the concentration limit of GB / T14848-2017(III) (50 μg / L), and the F [specific ions] concentration is lower than the concentration limit of [specific ions] (50 μg / L). - The ion concentration is less than the concentration limit (1 μg / L) of GB / T14848-2017(Ⅱ). The phosphogypsum-based polymer grouting material exhibits good working performance (flowability, setting time, and bleeding rate), mechanical properties (compressive strength, flexural strength, and splitting tensile strength), and durability (resistance to seepage pressure), meeting the requirements for road grouting materials.

[0105] Example 4

[0106] (1) Preparation:

[0107] Preparation of alkali activator: Take a beaker of appropriate size and weigh out the required mass of distilled water. Add the weighed instant sodium silicate granules to the distilled water in 2-3 portions, stirring with a glass rod each time until the solution becomes uniform in color and free of precipitate before adding more. Pour the flake NaOH from the small beaker into the above liquid (this releases a large amount of heat, so be careful). Then, use a magnetic stirrer to stir thoroughly at low speed for 10 minutes until the liquid is uniform in color and free of flocculent precipitate. Finally, remove the well-stirred mixture, seal the mouth of the beaker with polyethylene film, and age for 3 hours to obtain the alkali activator.

[0108] Weigh out the following components according to their mass fractions: 16.86% phosphogypsum, 7.81% ceramic waste, 9.28% metakaolin, 4.38% alkali activator, 9.44% water, 0.34% waterproofing additive, and 51.89% iron tailings sand. The weight ratio of water to ceramic waste, metakaolin, and phosphogypsum is 0.28; the total weight ratio of phosphogypsum, ceramic waste, and metakaolin to iron tailings sand is 0.67; and the weight ratio of phosphogypsum, ceramic waste, and metakaolin is 1:0.45:0.55. Check and verify the instruments used, clean and dry the cement mortar mixing pot, and set it aside for use.

[0109] (2) Preparation of geopolymer grouting material: Pour the weighed phosphogypsum, metakaolin, ceramic waste and iron tailings into a dry cement paste mixing pot and stir for 1 minute. Then pour in the pre-prepared alkali activator and waterproofing additive and stir evenly to obtain phosphogypsum-based polymer grouting material.

[0110] (3) Molding and curing: Before the experiment, clean the inside and surface of the mold, then apply machine oil evenly to its inner wall. After the geopolymer grouting material is mixed, pour it into the mold to 1 / 2 height, place it on the vibration table and vibrate for 1 minute, then fill the mold and vibrate for another 1 minute. Then use a scraper to smooth the surface to ensure that no air bubbles are generated. After the specimen is molded, let it stand at room temperature for 24 hours before demolding to obtain the molded specimen.

[0111] The molded specimens were placed in a standard curing chamber and cured for 3 days, 7 days, 14 days, and 28 days at a temperature of 20±5℃ and a relative humidity of ≥95%. Their working properties, such as fluidity, setting time, and water seepage, as well as their strengths at 3 days, 7 days, 14 days, and 28 days, including unconfined compressive strength, flexural strength, and splitting tensile strength, and their durability properties, such as impermeability, freeze-thaw resistance, and heavy metal leaching characteristics, were tested. The test results are shown in Table 1.

[0112] As shown in Table 1, the fluidity, setting time, and bleeding properties of the phosphogypsum-based polymer grouting material prepared in this embodiment all meet the technical requirements of DG / TJ 08-2240-2017. The 28-day unconfined compressive strength of the specimen is 7.86 MPa, which meets the technical requirement of DG / TJ 08-2240-2017 that the 28-day compressive strength of the grouting material should not be less than 4.2 MPa. The leachate from the specimen contains As, Pb, Cr, and F... - and PO4 3- The concentrations of the ions were 2.64 μg / L, 7.65 μg / L, 21.67 μg / L, 1.16 mg / L, and 0.75 mg / L, respectively. The samples contained As, Pb, Cr, and F. - and PO4 3-The ion concentrations of [specific ions] are significantly lower than those of phosphogypsum. Specifically, the As ion concentration is lower than the concentration limit of GB / T14848-2017(III) (10 μg / L), the Pb ion concentration is lower than the concentration limit of GB / T14848-2017(III) (10 μg / L), the Cr ion concentration is lower than the concentration limit of GB / T14848-2017(III) (50 μg / L), and the F [ion concentration] is lower than the concentration limit of [specific ions]. - The ion concentration is less than the concentration limit (2 μg / L) of GB / T14848-2017(Ⅳ). The phosphogypsum-based polymer grouting material exhibits good working performance (flowability, setting time, and bleeding rate), mechanical properties (compressive strength, flexural strength, and splitting tensile strength), and durability (resistance to seepage pressure), meeting the requirements for road grouting materials.

[0113] Table 1

[0114]

[0115]

[0116] The test methods and experimental conditions for each item in Examples 1-4 are as follows:

[0117] (a) Performance

[0118] This experiment, conducted in accordance with the "Test Procedures for Cement and Cement Concrete in Highway Engineering" (JTG3420-2020), tested the fluidity, setting time, and water bleeding properties of phosphogypsum-based polymer grouting materials.

[0119] (b) Mechanical properties

[0120] This experiment used the 28-day strength value to characterize the strength properties of the phosphogypsum-based polymer grouting material. The experimental control conditions were as follows: the specimens were 70.7mm×70.7mm×70.7mm cubic blocks and 40mm×40mm×160mm prismatic specimens. The molded specimens were cured at a temperature of 20±5℃ and a relative humidity of over 95% for 3d, 7d, 14d, and 28d. The flexural strength of the 40mm×40mm×160mm prismatic specimens was tested using a microcomputer servo press. The prismatic specimens that failed the flexural strength test were used for compressive strength testing. The 70.7mm cubic blocks were used for splitting tensile strength testing. The loading rate of the press was 0.3mm / min.

[0121] (c) Durability

[0122] This experiment used 28-day impermeability pressure to characterize the strength characteristics of phosphogypsum-based polymer grouting materials, and the residual freeze-thaw strength ratio (BDR) after 7 days of curing and 5 freeze-thaw cycles to characterize the freeze-thaw performance of phosphogypsum-based polymer grouting materials (see Equation 1). The experimental control conditions were as follows: the specimen size for the impermeability test was a frustum mold with upper and lower diameters of 7cm and 8cm respectively, and a height of 3cm. The molded specimens were cured for 7 days and 28 days at a temperature of 20±5℃ and a relative humidity of over 95%. After applying silicone sealant to the sidewalls of the specimens, they were placed in a mortar impermeability tester, and silicone sealant was continued to be applied to seal the edge gaps to prevent leakage during the experiment. After the silicone sealant cooled, the impermeability test was conducted. The initial water pressure was set at 0.2MPa, maintained for 2 hours, and then automatically increased by 0.3MPa. Afterward, it increased by 0.1MPa every hour, and the water pressure was recorded when water seeped from the top of the specimen. The specimens used in the freeze resistance test were cubic blocks with a side length of 70.1 mm. After curing the molded specimens at a temperature of 20±5℃ and a relative humidity of over 95% for 28 days, they were immersed in water at around 20℃ for 48 hours. After immersion, the specimens were placed in a low-temperature chamber that had been pre-cooled to -15℃ and frozen for 4 hours. Then, the specimens were removed and placed in water at around 20℃ for thawing for 4 hours. This was one freeze-thaw cycle.

[0123] (d) Characteristics of heavy metal leaching

[0124] This experiment employed a 7-day dynamic cyclic leaching test of heavy metals to evaluate the environmental impact of polymer grouting materials on phosphogypsum-based substrates, in accordance with the "Groundwater Quality Standard" (GB / T14848-2017). The test control conditions were as follows: specimen dimensions were 70.7mm × 70.7mm × 70.7mm.

[0125] BDR = (R) DC / R C )*100 (1)

[0126] In the formula, BDR is the residual strength ratio of the specimen after n freeze-thaw cycles, expressed as a percentage (%). DC R represents the compressive strength of the specimen after n freeze-thaw cycles, in MPa. DC The standard compressive strength of the specimen.

[0127] Compared with ordinary silicate cement-based grouting materials, the price of the phosphogypsum-based polymer grouting material of this invention is much lower than that of similar cement-based grouting materials and epoxy resin grouting materials on the market. The prices of the two are 3.35 times and 7.09 times that of phosphogypsum grouting materials (mortar-to-gel ratio 0.75), respectively, and the performance meets the specifications. This indicates that the phosphogypsum-based polymer grouting material of this invention can replace cement-based grouting materials, which not only saves cement usage but also has lower costs, and has the advantages of energy saving, environmental protection and economy.

[0128] Raw material prices

[0129]

[0130] Material usage and cost of polymer grouting material for phosphogypsum base with a mortar ratio of 0.6 per ton

[0131]

[0132] Price comparison of similar surface grouting materials

[0133]

[0134] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A phosphogypsum-based polymer road grouting material, characterized in that, The raw materials, by mass percentage, include the following components: The composition includes 16.86%-19.11% phosphogypsum, 7.81%-8.60% ceramic waste, 9.28%-10.51% metakaolin, 4.38%-5.22% alkali activator, 8.41%-9.44% distilled water, 0.34%-0.37% waterproofing additive, and 47.78%-51.89% iron tailings. The ceramic waste, metakaolin, and phosphogypsum constitute the adhesive material system. The weight ratio of water to the adhesive material system is 0.22-0.28; the weight ratio of the adhesive material system to the iron tailings is 0.65-0.80; and the weight ratio of phosphogypsum, ceramic waste, and metakaolin is 1:0.45:0.

55. Under the action of the alkali activator, the phosphogypsum-based polymer road grouting material exhibits a three-dimensional network aluminosilicate gel structure. The waterproofing additive is a sodium methylsilicate solution.

2. The phosphogypsum-based polymer road grouting material according to claim 1, characterized in that, The unconfined compressive strength, flexural strength, and splitting tensile strength of the polymer road grouting material based on phosphogypsum reached 5.84-11.56 MPa, 0.61-2.41 MPa, and 0.32-0.67 MPa, respectively, after 28 days of curing.

3. The phosphogypsum-based polymer road grouting material according to claim 1, characterized in that, The fluidity of the phosphogypsum-based polymer road grouting material reaches 199-235 mm, the setting time reaches 214-387 min, and the water bleeding rate reaches 0.2%-0.9%.

4. The phosphogypsum-based polymer road grouting material according to claim 1, characterized in that, The polymer road grouting material based on phosphogypsum base achieved a maximum impermeability pressure of 1.1 MPa after 28 days of curing.

5. The phosphogypsum-based polymer road grouting material according to claim 1, characterized in that, The alkaline activator is a compound of sodium hydroxide and sodium silicate.

6. The phosphogypsum-based polymer road grouting material according to claim 1, characterized in that, The phosphogypsum has a particle size between 0.1 and 600 μm, and the content of phosphogypsum particles with a particle size of less than 200 μm is ≥84%. The ceramic waste mainly consists of SiO2 and Al2O3, with a combined content of ≥88%. The particle size of the ceramic waste is 15-45 μm; The metakaolin mainly consists of SiO2 and Al2O3, with a combined content of ≥97.39%. The iron tailings sand is a solid waste discharged after iron ore is refined. It is obtained through crushing, grinding, washing and refining processes. The particle size of the iron tailings sand is concentrated in the range of 0.36-0.85mm.

7. A method for preparing a phosphogypsum-based polymer road grouting material according to any one of claims 1-6, characterized in that, Includes the following steps: (1) Preparation: Prepare the alkali activator in advance and age it for later use. Weigh out the required mass of phosphogypsum, ceramic waste, metakaolin, alkali activator, distilled water, waterproofing additive and iron tailings sand. (2) Preparation of geopolymer grouting material: The weighed phosphogypsum, ceramic waste, metakaolin and iron tailings sand are mixed and stirred. Then, an alkali activator and a waterproofing additive are added and stirred evenly to obtain a phosphogypsum-based polymer grouting material.

8. The method for preparing a phosphogypsum-based polymer road grouting material according to claim 7, characterized in that, The preparation process of the alkaline activator is as follows: Weigh out the required mass of flake NaOH and instant sodium silicate granules; Add the instant sodium silicate granules to distilled water in several batches, stirring after each addition until the solution becomes cloudy, uniform, and free of precipitate, then continue adding. Pour flake NaOH into a sodium silicate solution and stir magnetically until the liquid is uniform in color and free of flocculent precipitate to obtain an alkaline activator.

Citation Information

Patent Citations

  • Regenerative ceramic powder geopolymer repair mortar and preparation method thereof

    CN114213094A

  • High-durability iron tailing hydraulic road base material and preparation method thereof

    CN114315299A